PENGARUH RETURN ON ASSETS, EARNING PER SHARE, DAN GROSS DOMESTIC PRODUCT TERHADAP PRICE BOOK VALUE PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ-45 DI BURSA EFEK INDONESIA - B31111061, ISMAIL SIREGAR (Jurnal Manajemen Update, 2016)
PBV is the relationship between stock market price and book value per share. This ratio measures the value given by financial market to the management and organization as a firm continuous to grow. PBV shows ability of firm creating a relative value of the firm toward the capital invested. The higher the ratio PBV, The more successful the firm creating a value for shareholders. This study is aimed to examine the influence of return on assets, earning pershare, and gross domestic product toward price book value. Population of this study is all indeks LQ-45 firm listed on IDX during 2010-2014. By using purposive sampling, the written got 42 firm to be the sample. This study used multiple regression analysis , in previously, the data were examined using classical assumption test such as test of normality, multicolinierity, linearity, heteroskedastisitas and autocorrelation. The results of this study show the return on assets, earnings per share and gross domestic product jointly significant effect on the price-book value of the test f visits count of 12 180 with a probability of 0.000. Since the probability is much smaller than 0.05 or 5%, while individually, seen from the t test in which the probability is much greater than the level of significance of 0.05 or 5% that causes Pershare earnings and gross domestic product did not significantly related to the book value price. Key word : Return On Assets, Earning Pershare, Gross Domestic Product, Price Book Value